A CONTRIBUIÇÃO DO TRABALHO COLABORATIVO DO PROFESSOR DA SALA DE RECURSOS MULTIFUNCIONAIS COM OS PROFESSORES DO ENSINO COMUM - Rocha, Maria Rozane Cabral da (2020)
The research presented here delevoped a study on the educational practice involving the collaborative work of a teachers of the Multifunctional Resources room with two common classroom teachers and two students with autism spectrum disorder enrolled im a